How Important is Sovereign Risk in Determining Corporate Default Premia? The Case of South Africa - Peter, Marcel (International Monetary Fund, 2005)
The paper analyzes and quantifies the importance of sovereign risk in determining corporate default premia (yield spreads). It also investigates the extent to which the practice by rating agencies and banks of not rating companies higher than their sovereign (""country or sovereign ceiling"") is reflected in the yields of South African local-currency-denominated corporate bonds. The main findings are: (i) sovereign risk appears to be the single most important determinant of corporate default premia in South Africa; (ii) the sovereign ceiling (in local-currency terms) does not apply in the spreads of the industrial multinational companies in the sample; and (iii) consistent with rating agency policy, however, the sovereign ceiling appears to apply in the spreads of most financial companies in the sample